Determinants of traditional birth attendant utilisation among reproductive age women in Ethiopia: a multilevel analysis of the 2019 Ethiopian Demographic and Health Survey - Biruk Beletew Abate; Gizachew Yilak; Alemu Birara Zemariam; Befkad Derese Tilahun; Tegene Atamenta Kitaw; Molla Azmeraw Bizuayehu; Mulat Ayele; Addis Wondmagegn Alamaw; Eyob Shitie Lake (BMJ Open)
Objectives To identify the determinants of traditional birth attendants’ utilisation among reproductive-age women in Ethiopia.Design Cross-sectional study design.Setting Ethiopia.Participants A total of 3979 weighted samples of reproductive-age women were included.Outcome measure Traditional birth attendant utilisation.Results This study found a high prevalence (29.76%) of Ethiopian mothers using traditional birth attendants for delivery, based on data from the 2019 Ethiopian Demographic and Health Survey. Mothers with higher education (adjusted OR (AOR)=0.11, 95% CI: 0.01 to 0.62), who had four or more antenatal care visits (AOR=0.34, 95% CI: 0.21 to 0.54), communities with lower levels of education (AOR=2.21, 95% CI: 1.30 to 3.73), communities with higher poverty levels (AOR=1.71, 95% CI: 1.99 to 2.96) and those from peripheral regions (AOR=3.41, 95% CI: 1.77 to 6.56) were found to be predictors of traditional birth attendants.Conclusion This study indicates a high prevalence (29.76%) of Ethiopian mothers using traditional birth attendants, highlighting the need for targeted interventions to promote skilled birth attendance. Policymakers should focus on implementing educational programmes targeting reproductive-age women and improving access to quality antenatal care. Specific initiatives could include community-based educational workshops and subsidies for transportation to healthcare facilities. Furthermore, mothers in remote and border districts should receive specialised attention in terms of resource allocation, including skilled personnel and enhanced healthcare access.